A role of NLRP3 and MMP9 in migraine progression: a systematic review of translational study - Rushendran, Rapuru; Singh, Anuragh; Ankul Singh, S.; Chitra, Vellapandian; Ilango, Kaliappan (Frontiers in Neurology, 2024)
Background Migraines affect one billion individuals globally, with a higher occurrence among young adults and women. A significant survey in the United States indicated that 17.1% of women and 5.6% of men suffer from migraines. This study seeks to investigate the potential connection between NLRP3 and MMP9 in migraine pathology. Methods The research involved searching databases such as PubMed, Scopus, Science Direct, Google Scholar, and Proquest, with the search concluding on March 31, 2024. Following PRISMA guidelines, PICO data were collected, focusing exclusively on animal models induced by Nitroglycerine (10 mg/kg), while excluding clinical studies. Results The study, originally registered in Prospero Reg. No. CRD42022355893, conducted bias analysis using SYRCLE’s RoB tool and evaluated author consensus using GraphPad v9.5.1. Out of 7,359 search results, 22 papers met the inclusion criteria. Inter-rater reliability among reviewers was assessed using Cohen’s kappa statistics. Conclusion This review summarizes 22 preclinical studies on Nitroglycerin (NTG), NLRP3, MMP9, and related biomarkers in migraine. They reveal that NTG, especially at 10 mg/kg, consistently induces migraine-like symptoms in rodents by activating NLRP3 inflammasome and stimulating proinflammatory molecule production. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, CRD42022355893.